The Relationship between Physical Fitness and Reasoning in Community-Dwelling Older Adults. Issue 3 (3rd July 2022) - Tommerdahl, Jodi; Biggan, John; McKee, Fred; Nesbitt, Monica; Ray, Christopher
ABSTRACT: This study examines two independent aspects of cognition, deductive and probabilistic reasoning to differentiate between their relationship to physical fitness in older adults. This study measured the deductive and probabilistic reasoning abilities of 65 community dwelling older adults ranging in age from 55 to 92 ( M = 74.88, SD  = 6.70). A series of three-line syllogisms was used to measure both probabilistic and deductive reasoning while physical testing was carried out using the Senior Fitness Test (SFT). Results showed deductive reasoning to be positively correlated with the SFT, particularly lower body strength (chair stands; r = .40), aerobic fitness (2-minute step test; r = .37), and agility/dynamic balance (8-foot up-and-go [smaller score is better]; r = −.29). However, no relationship was found between physical fitness and probabilistic reasoning.